Exploratory wine consumer behavior in a transitional market: The case of Poland - Renata Schaefer; Janeen E. Olsen; Liz Thach (Wine Economics and Policy, 2018)
This paper investigates exploratory behavior among wine consumers in Poland where the country's wine culture is in a state of rapid change. This study investigates the extent to which demographics, values, and wine preferences relate to exploratory behavior. Data obtained from 198 Polish wine consumers was used in the analysis. Exploratory behavior was measured using the VARSEEK scale adapted to wine. Other measures included the Schwartz Value Inventory, wine knowledge and involvement, and measures relevant for wine purchasing behavior. Demographic variables were also used to profile consumers. The findings show that Polish wine consumers' level of exploratory behavior is not related to demographics, but is influenced by personal values. The consumers who were most likely to engage in exploratory behavior valued creativity, fun, and risk taking and were less concerned about behaving properly. They also had more global outlook as they were more likely to purchase wine in other countries and desired more wines from regions outside Poland. The findings are useful for wine marketers when developing strategies for wine consumers in transitional markets based on their unique needs and expectations. This is the first known research conducted in Poland focusing on wine consumers' exploratory behavior and subsequent wine preferences.
Keywords: 330; Consumer behavior; Consumer segmentation; Exploratory behavior; Polish wine market